Phenoxide-bridged Zinc(II)-Bis(dipicolylamine) Probes for Molecular Imaging of Cell Death - Clear, Kasey J. (Bioconjug Chem, 2015)
Cell death is involved in many pathological conditions, and there is a need for clinical and preclinical imaging agents that can target and report cell death. One of the best known biomarkers of cell death is exposure of the anionic phospholipid phosphatidylserine (PS) on the surface of dead and dying cells. Synthetic zinc(II)-bis(dipicolylamine) (Zn(2)BDPA) coordination complexes are known to selectively recognize PS-rich membranes and act as cell death molecular imaging agents. However, there is a need to improve in vivo imaging performance by selectively increasing target affinity and decreasing off-target accumulation. This present study compared the cell death targeting ability of two new deep-red fluorescent probes containing phenoxide-bridged Zn(2)BDPA complexes. One probe was a bivalent version of the other, and associated more strongly with PS-rich liposome membranes. But, the bivalent probe exhibited self-quenching on the membrane surface, so the monovalent version produced brighter micrographs of dead and dying cells in cell culture and also better fluorescence imaging contrast in two living animal models of cell death (rat implanted tumor with necrotic core and mouse thymus atrophy). An (111)In-labelled radiotracer version of the monovalent probe also exhibited selective cell death targeting ability in the mouse thymus atrophy model, with relatively high amounts in dead and dying tissue and low off-target accumulation in non-clearance organs. The in vivo biodistribution profile is the most favorable yet reported for a Zn(2)BDPA complex and thus the monovalent phenoxide-bridged Zn(2)BDPA scaffold is a promising candidate for further development as a cell death imaging agent in living subjects.